2008
DOI: 10.1128/mcb.01075-08
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Recruitment of BRCA1 to DNA Double-Strand Breaks Is Dependent on Its Association with Ku80

Abstract: BRCA1 is the first susceptibility gene to be linked to breast and ovarian cancers. Although mounting evidence has indicated that BRCA1 participates in DNA double-strand break (DSB) repair pathways, its precise mechanism is still unclear. Here, we analyzed the in situ response of BRCA1 at DSBs produced by laser microirradiation. The amino (N)-and carboxyl (C)-terminal fragments of BRCA1 accumulated independently at DSBs with distinct kinetics. The N-terminal BRCA1 fragment accumulated immediately after laser ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 54 publications
1
69
0
4
Order By: Relevance
“…Previously, we showed that BRCA1 promotes precise rejoining of DSBs in human breast carcinoma cells while suppressing microhomology-mediated error-prone end joining and restricting sequence deletion at the break junction during repair (34). In addition, BRCA1 interacts with Ku80, which may be required for BRCA1-Ku80 foci formation in response to laser-induced DSBs (35). BRCA1 also interacts with the Mre11⅐Rad50⅐Nbs1⅐CtIP supercomplex and is critical for the function of CtIP in HR.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that BRCA1 promotes precise rejoining of DSBs in human breast carcinoma cells while suppressing microhomology-mediated error-prone end joining and restricting sequence deletion at the break junction during repair (34). In addition, BRCA1 interacts with Ku80, which may be required for BRCA1-Ku80 foci formation in response to laser-induced DSBs (35). BRCA1 also interacts with the Mre11⅐Rad50⅐Nbs1⅐CtIP supercomplex and is critical for the function of CtIP in HR.…”
Section: Discussionmentioning
confidence: 99%
“…40 Finally, Ku80 was shown to recruit BRCA1 to sites of DSB. 41 As BRCA1 is a mediator of the HR function of Rad51, 42 lack of Ku80 may have impact also on HR on blocked replication forks. Thus, the data suggests that Ku80 has multiple functions related to the recognition and recruitment of repair factors, including HR proteins, to the site of DSB induced upon ICL processing.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that BRCA1 associates only with Ku in G 1 but forms a distinct complex with MRN and CtIP upon entry into S phase in order to activate the MRN nuclease activity to initiate resection. The N terminus of BRCA1 interacts with both Ku and Nbs1, but mutants differentially affected for either interaction are not yet available (82,100,101). Whether the MRN nuclease activity is required for Ku removal in mammalian cells remains an open question, but recent advances in assessing Ku localization should allow this important experiment to be done (102).…”
Section: Removal Of Ku From Dsb Endsmentioning
confidence: 99%